Infant Burial Practices as Domestic Funerary Ritual at Early Bronze Age Titriş Höyük - Matney, Timothy ca. 20./21. Jh. (Near Eastern archaeology, 2018)
The Early Bronze Age tradition of intramural tombs at settlements in the Middle Euphrates region is well established, with examples from many excavations. Often these intramural tombs comprise stone-built cist chambers with adult or juvenile occupants and a range of funerary offerings. They are located within domestic residences and interpreted as family crypts. Less well explored are contemporary infant burials, which, in addition to poor preservation, are often located beneath the living floors of domestic houses but not within the cist tombs. This study reviews the evidence for the intramural burial of infants at mid-to late Early Bronze Age Titriş Höyük in southeastern Turkey in the context of broader funerary traditions at the site and in the region. The author suggests that the division between adult/juvenile and infant burial treatments might be more pragmatic than dogmatic; the implications of this observation for domestic funerary rituals and household cults are explored.